Cervical cancer survival times in Africa - Drokow, Emmanuel Kwateng; Fangninou, Fangnon Firmin; Effah, Clement Yaw; Agboyibor, Clement; Zhang, Yunfeng; Arboh, Francisca; Deku, Marie-Anne; Xinyin, Wu; Wang, Yue; Sun, Kai (Frontiers in Public Health, 2022)
Objective: Accessibility to quality healthcare, histopathology of tumour, tumour stage and geographical location influences survival rates. Comprehending the bases of these differences in cervical cancer survival rate, as well as the variables linked to poor prognosis, is critical to improving survival. We aim to perform the first thorough meta-analysis and systematic review of cervical cancer survival times in Africa based on race, histopathology, gender, geographical location and age and juxtapose them with survival rates patterns in America. Methods and Materials: Major electronic databases were searched for articles published about cervical cancer survival rate in Africa. The eligible studies involved studies which reported 1-year, 3-year or 5-year overall survival (OS), disease-free survival (DFS) and /or locoregional recurrence (LRR) rate of cervical cancer patients living in Africa. Two reviewers independently chose the studies and evaluate the quality of the selected publications, in accordance with acceptable standards. We used random effects analysis to pooled the survival rate across studies and heterogeneity was explored via sub-group and meta-regression analyses. A leave-one-out sensitivity analysis was undertaken, as well as the reporting bias assessment. Our findings were reported in accordance with the accepted reporting criteria. Results: A total of 16,122 women with cervical cancer were covered in the 45 articles (59 studies), with research sample sizes ranging from 22 to 1059 (median = 187.5). The five-year overall survival (OS) rate was 40.9% (95% CI: 35.5–46.5%). The five-year OS rate ranged from 3.9% (95% CI: 1.9–8.0%) in Malawi [18] to as high as 76.1% (95% CI: 66.3–83.7%) in Ghana. The five-year disease-free survival rate was 66.2% (95% CI: 44.2–82.8%) while the five-year locoregional rate survival was 57.0% (95% CI: 41.4%–88.7%). Conclusion: To enhance cervical cancer survival, geographical and racial group health promotion measures, as well as prospective genetic investigations, are critically required.